Association between depressive state and behavioral changes induced by the state of emergency for Coronavirus disease 2019: Evidence from university students in Japan - Takafumi Ogawa (Elsevier, 2021)
Coronavirus disease 2019 (Covid-19) has caused numerous problems worldwide since 2020. The pandemic and subsequent quarantine policies have resulted in numerous psychological problems among students. The quarantine policy forced students to change their behavior and refrain from going out. To date, the relationship between behavioral and psychological changes following the implementation of the quarantine policy has not been investigated. We conducted a web-based survey to investigate the change in time spent out of the house between before and after the implementation of the quarantine policy and how this related to changes in depression. We collected data from 12,088 students, which included the Patients Health Questionnaire-9, frequency of going out, and demographics. We divided subjects into three categories based on the frequency of going out before and after the policy was put in place. Results showed that students who frequently went out before the pandemic and strictly followed the government policy were significantly more depressed than those who did not frequently go out. In contrast, students who had always been reluctant to go out did not have a tendency for depression to worsen. Our findings indicate that behavioral modification leads to depression in those who previously had active social lives.